Peningkatan Kapasitas Mahasiswa dalam Manajemen Informasi dan Etika Pemberitaan melalui Eksplorasi Media Massa - Novia, Lely; Mustikawati, Yunitari; Asriati, Asriati; Hajar, Andi; Amaliah, Suci (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service activity aims to enhance students' capacity in information management and news ethics through direct exploration of mass media institutions. The methods used include journalism training, mini research projects, and direct visits to various media outlets such as TVRI, Kompas TV, iNews, Tribun Timur, Herald.id, Derap Hukum, Media Sulsel, Ujung Jari, Koran Makassar, and Beritakota. Students were divided into 12 groups and conducted simple research related to current media issues. The results of this activity indicate a significant improvement in students' analytical skills, understanding of journalistic ethics, and ability to process information in the digital era. Moreover, direct interaction with professional journalists deepened their understanding of the challenges faced in the media industry. The project also successfully produced articles and reports that were published in local media and the department's official website. This activity demonstrates that field-based practical experience is essential in equipping students with relevant and adaptive skills to face the rapidly evolving dynamics of information in society.